2009
DOI: 10.1210/jc.2008-0708
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Preservation in Girls with Turner Syndrome: Prognostic Signs of the Presence of Ovarian Follicles

Abstract: Signs of spontaneous puberty, mosaicism, and normal hormone concentrations were positive and statistically significant but not exclusive prognostic factors as regards finding follicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(80 citation statements)
references
References 30 publications
0
79
0
1
Order By: Relevance
“…Borgstrom et al examined predictors for the presence of follicles and concluded that follicles were more likely to be found in girls with a mosaic karyotype, a low FSH level, a high antimüllerian hormone level, spontaneous onset of puberty, and spontaneous menarche 19 . Consistent with these reports, the 2 of 3 Turner cases in our study showed AMH levels within normal levels (>1.1 ng/mL), but diminished for their age.…”
Section: Discussionmentioning
confidence: 99%
“…Borgstrom et al examined predictors for the presence of follicles and concluded that follicles were more likely to be found in girls with a mosaic karyotype, a low FSH level, a high antimüllerian hormone level, spontaneous onset of puberty, and spontaneous menarche 19 . Consistent with these reports, the 2 of 3 Turner cases in our study showed AMH levels within normal levels (>1.1 ng/mL), but diminished for their age.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Anywhere from 1/4 to 2/3 of ovarian tissue is removed for cryopreservation purposes leaving a partially intact ovary in situ. 17,18,20,22,24,25 In many cases, the right ovary was selected due to its preferred anatomic location away from the sigmoid colon. 26 Dissection was carried out with the use of sharp scissors out of fear for follicle damage secondary to electrocautery burn.…”
Section: Resultsmentioning
confidence: 99%
“…18,20,22,24 One incident of clinically significant intraoperative blood loss requiring transfusion was described in a pediatric patient. 23 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictors for successful autologous IVF include a mosaic peripheral blood karyotype, normal serum FSH and AMH levels, and spontaneous puberty. Negative predictors for successful autologous IVF are monosomy or a structurally anomalous X chromosome, elevated FSH levels, low AMH levels, and lack of spontaneous puberty (22), (15), (26). …”
Section: Pregnancy In Turner Syndromementioning
confidence: 99%